Malaria in the State of Amazonas: a typical Brazilian tropical disease influenced by waves of economic development - Sampaio,Vanderson Souza (2015)
In Brazil, more than 99% of malaria cases are reported in the Amazon, and the State of Amazonas accounts for 40% of this total. However, the accumulated experience and challenges in controlling malaria in this region in recent decades have not been reported. Throughout the first economic cycle during the rubber boom (1879 to 1912), malaria was recorded in the entire state, with the highest incidence in the villages near the Madeira River in the Southern part of the State of Amazonas. In the 1970s, during the second economic development cycle, the economy turned to the industrial sector and demanded a large labor force, resulting in a large migratory influx to the capital Manaus. Over time, a gradual increase in malaria transmission was observed in peri-urban areas. In the 1990s, the stimulation of agroforestry, particularly fish farming, led to the formation of permanent Anopheline breeding sites and increased malaria in settlements. The estimation of environmental impacts and the planning of measures to mitigate them, as seen in the construction of the Coari-Manaus gas pipeline, proved effective. Considering the changes occurred since the Amsterdam Conference in 1992, disease control has been based on early diagnosis and treatment, but the development of parasites that are resistant to major antimalarial drugs in Brazilian Amazon has posed a new challenge. Despite the decreased lethality and the gradual decrease in the number of malaria cases, disease elimination, which should be associated with government programs for economic development in the region, continues to be a challenge.